Analog front end design for data acquisition system - Sng, Aldric Qing En (Nanyang Technological University, 2022)
Almost all circuit modelling software in our current technology has a graphical user interface (GUI). The user creates the circuit diagram by drawing components (such as resistors, capacitors, etc.) and connecting them with lines that indicate electrical connections. The outcome is a user-friendly schematic that also informs the simulation program about the circuit's connections which is much intuitive in comparison to FORTRAN, which is a well known high-level programming language for scientific applications in the earlier days of simulation programs. There are many different types of circuit simulators in the world such as NgSpice, GnuCap, EasyEDA, CircuitLogix, LTSpice and many more which are mainly used for circuit drawing, circuit design and circuit analysis. However, among all the circuit simulator software available to users, the best circuit simulation software considered is LTSpice. LTSpice is a high-performance circuit simulation application from Analog Devices that lets you draft, explore, and evaluate your circuit design's performance. LTSpice has a schematic editor, waveform viewer, and complex capabilities that are simple to use after you grasp the basics. For its macro models, LTSpice employs patented modelling approaches, resulting in quick and precise simulation results. This is especially crucial when designing switch-mode power supplies, as LTSpice outperforms many other simulation tools and allows you to repeat your designs quickly. The purpose of the report is to learn and recognize the process of simulation for a single ended to differential output amplifier with the aid and guidance of the LT Spice simulator software.